the effect of audio visual about health education towards the level of knowledge and dysmenorrhea handling attitude to the teenager - Ariani Fatmawati; Nden Ayu; Nina Gartika (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2021)
Every teenage girl experiences different menstrual experiences, some are menstruating without complaint and some are menstruating accompanied by complaints of dysmenorrhea. In fact, the knowledge and response of them are still lacking towards the handling of dysmenorrhea. The aim of this study was to determine the effect of audio visual about health education towards the level of knowledge and dysmenorrhea handling attitude to the teenager. The research design used was quantitative research with a pre-experimental type with a one-group pretest posttest design without control. The sampling technique in this study was conducted using non-probability sampling with purposive sampling technique, that was 30 respondents. The questionnaire used in this study is a knowledge and attitude questionnaire with the results of the validity test ≥ 0.3 and the reliability of knowledge of 0.936 and attitudes of 0.840. The inclusion criteria in this study were students who experienced dysmenorrhea and the exclusion criteria were students with gynecological diseases. On average, 47% of respondents' knowledge before the intervention had less knowledge and after the intervention 73% had good knowledge and attitudes before the intervention were in the negative category 70% and after the intervention was in the positive category 83%. Wilcoxon statistical test results obtained p value = 0.000 (p value ≤ 0.05). Suggestions that can be given was audiovisual media in the form of video can be an option as a media to provide health education. Suggestions in this study can be a reference for providing health education through audiovisuals for adolescents. The school can facilitate these activities and cooperate with local health offices.